Stress testing of real credit portfolios - Ferdinand Mager; Christian Schmieder (Deutsche Bundesbank, 2008)
Stress testing has become a crucial point on the Basel II agenda, mainly as Pillar I estimates do not explicitly take portfolio concentration into account. We start from the credit portfolio of the German pension insurer being a cross-sectional representation of the German economy and subsequently compose three bank portfolios corresponding to a small, medium and large bank. We apply univariate and multivariate stress tests both by using the Internal Rating based (IRB) model and by a model that additionally allows for variation of correlation. In a severe multivariate stress scenario based on historical data for Germany IRB capital requirements increase by more than 80% with little differences between the credit portfolios. If stress testing is additionally applied to correlation, the Value-at-Risk increases by up to 300% and portfolio differences materialize.
Keywords: G21; G28; 330; Credit Portfolio; Exposure concentration; Stress Testing; Basel II; Economic Capital; Kreditrisiko; Portfolio-Management; Value at Risk; Kreditwürdigkeit; Deutschland